An Experimental Study of the Gemination in Arabic Language - FERRAT, Kamel; GUERTI, Mhania (Archives of Acoustics, 2017)
In this paper, we report the results of an experimental study of the acoustic and articulatory features of the gemination in Modern Arabic language, pronounced by Algerian speakers. To extract the feature characteristics, we have carried out an acoustic analysis by computing the values of frequency formants, energy and durations of the consonants and subsequent vowels in the various [VCV] and [VCgV] utterances (Cg: geminate consonant). For the articulatory analysis, a range of kinematics parameters were analyzed from the phoneme productions including movement trajectories, distance, velocity, and duration of tongue movements. Among the most important results, we note a longer duration of the vowel following a geminate consonant, a decreasing in levels of F1 and F2 formants and a rising in level of F3 formant of this vowel.